Genome-wide identification and characterization analysis of CONSTANS-like gene family in wheat (Triticum aestivum L.) - Gao, Yameng; Wang, Ziqi; Kan, Wenjie; Yang, Zhu; Li, Zhiwei; Jian, Shuangling; Wang, Dacheng; Tang, Caiguo; Wu, Lifang (Frontiers in Plant Science, 2025)
The CONSTANS-like (COL) proteins are plant-specific transcription factors that play pivotal roles in growth, development, stress responses, and photoperiodic flowering. However, the CONSTANS-like (TaCOL) gene family in wheat (Triticum aestivum) remains inadequately characterized. In this study, we systematically identified 51 TaCOL genes in the wheat genome and classified them into three phylogenetic subfamilies (I, II, and III). Members within each subfamily shared conserved gene structures and motif compositions. Chromosomal location analysis revealed that the TaCOL genes were distributed across 15 chromosomes, with segmental duplication events identified as a major driver of this family expansion. Collinearity analysis among eight other Poaceae species further suggested that the TaCOL gene family was highly conserved and had undergone strong purifying selection during evolution. Promoter analysis uncovered numerous light-responsive and stress-related cis-elements, suggesting roles in environmental adaptation. Expression profiling demonstrated both tissue-specific and developmental stage-dependent patterns, and co-expression network analysis linked certain TaCOL genes to stress response and floral development pathways. Using qRT-PCR, we examined the expression of TaCOL genes under long-day and short-day photoperiods, revealing distinct expression patterns of several genes, including Ta-2B-COL4, Ta-5D-COL16, and Ta-7D-COL48. Furthermore, subcellular localization and transcriptional activation assays confirmed that the three proteins were nuclear localized and that Ta-5D-COL16 exhibited transcriptional activation activity. Together, these results provided valuable insights into the evolutionary history and molecular functions of TaCOL genes, establishing a foundation for future functional studies aimed at elucidating their roles flowering time regulation and environmental adaptation in wheat.